Sintesa Dan Karakterisasi Arang Aktif Dari Batang Tembaku Terkativasi Hcl Dengan Modifikasi Tio2 Dengan Proses Sonikasi - Nopiyanti, Wiwin; Latif, Ahmad Sofwan; Kurniati, Ely; Susilowati, Titi; Saputro, Erwan Adi (Universitas Nahdlatul Ulama Blitar, 2025)
Activated carbon is an adsorbent commonly used in adsorption methods for waste treatment due to its high adsorption capacity and simple preparation. Nevertheless, activated carbon also has limitations, such as low adsorption efficiency, which necessitates the use of supporting materials to resolve these weaknesses. TiO₂ a semiconductor material used in photocatalysis for waste treatment, has the advantage of reducing contaminants through decomposition processes. Nevertheless, TiO₂ also has disadvantages, such as a low adsorption capacity and a tendency to agglomerate. To resolve the limitations of both activated carbon and TiO₂, a method of combining these materials is employed. The addition of TiO₂ to activated carbon through sonication disperses TiO₂ particles on the surface of the activated carbon particles, filling the pores inside the activated carbon structure and creating additional micro and mesopores. This process enhances the porosity and surface area of the activated carbon. This study is intended to determine the effect of TiO₂ addition ratio and HCl activator concentration on the quality of the activated carbon. The research methodology involves activating the carbon with HCl and addition of TiO₂ in specific ratios through sonication. The best results were obtained with a treatment using 1 M HCl concentration and 5% TiO₂ addition ratio, which resulted in activated carbon with a surface area of 4257 m²/g. The addition of TiO₂ to HCl-activated carbon significantly increases the surface area compared to activated carbon without TiO₂.